Predictive influence of sociodemographic characteristics and the type of developmental disorder on children’s adaptive achievements - Sladjana Ćalasan; Nadica Jovanović-Simić; Bojana Drljan (Биомедицинска истраживања, 2025)
Introduction: Adaptive behavior, which includes conceptual, social, and practical skills, is a key indicator of children’s dai ly functioning. Its assessment is particularly important in identifying intellectual disabilities, as well as in evaluating the developmental potential of children with various developmental disorders and those with typical development. The aim of this study was to examine the predictive power of sociodemographic factors and type of develop mental disorder in relation to children’s adaptive achievements. Methods: The study was conducted on a sample of 183 children, aged 4 to 14 years, divided into four groups: children with developmental language disorder (DLD), autism spectrum disorder (ASD), mild intellectual disability (MID), and typically developing children (TD). Data were collected using a specially designed questionnaire and the Adaptive Behavior Diagnostic Scale (ABDS). Results: Regression analysis showed that the type of developmental disorder was the strongest predictor of adaptive functioning across all examined domains. The number of siblings was also a significant predictor of the overall adaptive score and most individual domains, except the social domain. Family income emerged as the significant predictor in the conceptual domain. Conclusion: The type of developmental disorder has a dominant influence on children’s adaptive achievements, while certain sociodemographic variables additionally contribute to explaining variations in adaptive behavior. These findings highlight the need for an individualized approach in assessment and intervention planning.
Keywords: adaptive behavior; developmental disorders; sociodemographic characteristics; children